Rancangan Aplikasi Smart City Berbasis Mobile Untuk Meningkatkan Kulitas Layanan Publik Studi Kasus Pemkot Bogor - Enok Tuti Alawiah (Universitas Bina Sarana Informatika, 2017)
Bogor City is an urban city with a geographic location close to the state capital, has a growing community of various groups became the basis of good economic growth when applying the concept of smart city. Bogor city continues to grow and improve to meet the era of free competition towards the Asean Economic Community. Mobile based application is an application that is most appropriately used as a connecting device between the city of Bogor and the general public. Mobile based application can be accessed easily using smartphones general public that can be used to report information related to public services, to find out information and government policies and can also be accessed by governments and stakeholders in the government who can provide feedback directly to the public. Systems development method waterfall method Pressman (2010:39), which includes five phases, namely Communication, planning, modeling, construction, deployment. Analysis of pemanfaataan mobile-based applications can use big data. Analysis of big data captured includes data sets stored in large quantities (volume), the need to access large data sets quickly (Velocity), the format of the data that are more varied (Variety). The benefits of big data carried analias can do a lot of cost savings and budget, making decisions and new innovation, and measuring satisfaction and public services.Keyword: city, big data, kotabogor, mobile aplication